Teknologi Kinerja Pastoral - Vinsensius Nase (STIPAS St. Sirilus Ruteng, 2020)
The title of this writing is Pastoral PerformanceTechnology. Technology is all hardware and software things of technology. Technology can be used to facilitate human activities without exception. Performance is achievement, in meaning quality and quantity of human as a personal or organization achievement. Pastoral is all apostolic activities of the catholic Church consist of teaching task, proclaiming task, sanctifying task and leading task for the people of the church. The main question of this writing is what is the main contribution of Pastoral Performance Technology to pastoral activities. That is why, the purpose of this writing is to describe and explain pastoral performance technology and its contribution in apostolic activities of the Church. Pastoral Performance technology gives contribution to facilitate a systematic planning in pastoral activities and systemic results. The Second Concilium of the Vatican advised the church to use technology in apostolic/pastoral activities. Contribution of pastoral performance technology is all pastoral activities must be started of planning, development, using, management and evaluation of pastoral activity. Pastoral pattern in spirit of pastoral performance technology is holistic integrative pastoral.